(untitled) (Research, Society and Development, 2022)
Alzheimer’s Disease (AD) represents the leading cause of dementia worldwide. Examples of promising approaches in the investigation of products against AD is the in vitro evaluation of acetylcholinesterase enzyme inhibition and protection against oxidative stress induced in neuronal cells by H2O2, already used in P. guajava extracts. In this work, the in vivo efficacy of P. guajava leaf extract in reversing scopolamine-induced working memory deficit will be evaluated. For that, 33 Swiss mice, male, albino (35-45g) were used. Control animals (Ctr) received saline, the memory deficit was induced by scopolamine 5 mg/kg (Esc). The ethanolic extract of P. guajava leaf (EFPG) was diluted in 5% ethanol in saline and administered at two different concentrations (EFPG 1 and 10 mg/kg). Scopolamine administration promoted the deficit in working memory (spontaneous changes: Ctr: 69.2 ± 4.9; Esc: 51.8 ± 5.0). At a dose of 10 mg/kg of EEPG, a partial block of memory deficit was observed (Esc + EEPG 10: 62.6 ± 3.1). No statistically significant changes were observed between the groups when the number of entries in the arms during the test was evaluated (Events: Ctr: 22.9±2.7; Esc: 28.1±2.9; Esc + EEPG 1: 25 .2±3.1; Esc + EEPG 10: 23.6±2.6). As anticholinesterase activity in vitro was reported for P. guajava leaf extract, the present work contributes to add evidence of its therapeutic potential for the treatment of Alzheimer’s Disease.